COVID-19’s impact on great-power competition (2020)
After the terrorist attacks on 9/11, the United States reoriented itself to focus on terrorist networks and rogue states. Congress created a new institution, the Department of Homeland Security. President George W. Bush made terrorism and counterproliferation the organizing principle of US national security policy. The administration adopted the 1% rule—if there was a 1% chance of something happening, it would be treated as an imminent danger. This doctrine would lead to the invasion of Iraq. Almost two decades later, the United States still wages a low-intensity, high-technology war against terrorist networks all over the world. The coronavirus has surpassed 9/11 and the global financial crisis as the defining international event for the majority of Americans. Over 130,000 Americans have died to date, and over forty million have lost their jobs. More people are dying from COVID-19 globally than almost anything else.1 The virus placed immense strain on globalization, brought travel to a virtual halt, exposed strains within the European Union, and poses the greatest challenge to the Chinese Communist Party since 1989. And that is as of this writing in June 2020. The crisis may be a long one that extends well into 2021.